Croatia : Where are We Since the COVID-19 Outbreak? - World Bank (World Bank, Washington, DC, 2021)
This report focuses on the impact of Coronavirus (COVID-19) outbreak in Croatia as of December 2020. The data was collected through the rapid response household surveys Survey representing Croatian households.